1989
DOI: 10.1111/j.1365-2044.1989.tb11102.x
|View full text |Cite
|
Sign up to set email alerts
|

Total intravenous anaesthesia for laparoscopy

Abstract: Key wordsAnaesthetic techniques; total intravenous. Anaesthetics, intravenous; ketamine, propofol.In a previous study' we showed that a total intravenous anaesthetic technique with a mixture of ketamine, midazolam and vecuronium was a safe, simple and reliable alternative to inhalational anaesthesia for use in the field, and the method was proposed as a substitute for use in general civilian practice. We decided to compare this technique with another form of total intravenous anaesthesia for a relatively short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…However, this finding of an uneventful postoperative course seems to be of importance, and accords with the results reported by Guit et al [4]. It has been shown that the use of a benzodiazepine, such as midazolam, lowers the incidence of psychological side effects [6]. It is possible that propofol could have the same effect.…”
Section: Discussionsupporting
confidence: 91%
“…However, this finding of an uneventful postoperative course seems to be of importance, and accords with the results reported by Guit et al [4]. It has been shown that the use of a benzodiazepine, such as midazolam, lowers the incidence of psychological side effects [6]. It is possible that propofol could have the same effect.…”
Section: Discussionsupporting
confidence: 91%
“…For these reasons, the combination of midazolam and ketamine has been previously recommended for total intravenous anesthesia [12][13][14], however, there are few reports on whether or not it is also useful for patients who have a history of allergy. Nevertheless, it is well known that combined H 1 -and H 2 -receptor antagonist reduces the number of histamine-related side effects [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine is useful for asthmatic patients [8], and its effectiveness and successful use in the anesthetic management of the asthmatic patients have both been reported [9][10][11]. The combination of midazolam with ketamine has also been previously recommended for total intravenous anesthesia in military surgery, general civilian practice and cardiac surgery [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In general anesthesia, ketamine has been used safely against allergic reactions, especially for asthmatic patients because of its advantages for relaxing tracheal smooth muscle [34,35], and its ability to treat bronchospasm [11,12]. Since midazolam attenuated both the cardiostimulatory responses and unpleasant emergence associated with ketamine [36], the combination of midazolam and ketamine has been recommended for total intravenous anesthesia [13][14][15]. In our previous study, the induction of anesthesia with midazolam-ketamine was shown to be useful for allergic patients without any significant problems [16].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the combination of midazolam and ketamine has been previously recommended for total intravenous anesthesia [13][14][15].…”
Section: Introductionmentioning
confidence: 99%